Causal associations between autoimmune diseases and sarcopenia-related traits: a bi-directional Mendelian randomization study - Chen, Chunlan; He, Ying (Frontiers in Genetics, 2024)
Background: Sarcopenia is common in patients with autoimmune diseases (ADs); however, the causal associations between ADs and sarcopenia remain unclear. Therefore, this study investigated the causal associations using bi-directional Mendelian randomization analysis. Methods: Exposure-related single-nucleotide polymorphisms (SNPs) were extracted from genome-wide association studies (GWASs). GWAS statistics for common ADs [Crohn’s disease (CD), ulcerative colitis (UC), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), psoriasis (PSO), and multiple sclerosis (MS)] and sarcopenia-related traits [hand grip strength (HGS), appendicular fat-free mass (FFM), and walking pace] were obtained from public datasets. Inverse-variance weighting as the main method was used to evaluate the causal effect. Results: Genetically predicted CD had causal effects on whole-body FFM (β = −0.005, p = 0.001), leg FFM (βleft = −0.006, p = 1.8E-4; βright = −0.007, p = 2.0E-4), and arm FFM (βleft = −0.005, p = 0.005; βright = −0.005, p = 0.001), while RA had causal effects on 8 sarcopenia-related traits, namely, HGS (βleft = −2.06, p = 2.8E-38; βright = −2.311, p = 2E-20), whole-body FFM (β = −0.842, p = 4.7E-10), leg FFM (βleft = −0.666, p = 2.6E-6; βright = −0.073, p = 2.1E-3), arm FFM (βleft = −0.63, p = 4.4E-6; βright = −0.736, p = 4.4E-8), and walking pace (β = −1.019, p = 6.2E-14). In the reverse direction, HGS (odds ratio [OR]left = 10.257, p = 3.6E-5; ORright = 16.445, p = 3.7E-7) had causal effects on CD, while HGS (ORleft = 0.994, p = 0.004; ORright = 0.993, p = 1.4E-4), leg FFM (ORleft = 1.003, p = 0.005; ORright = 1.005, p = 1.9E-4), and walking pace (OR = 0.985, p = 5.7E-5) were causally associated with RA. No evidence showed causal associations of UC, SLE, PSO, or MS with sarcopenia-related traits. Conclusion: Our study demonstrated that the genetic susceptibility to CD and RA was associated with high risk of sarcopenia, and some sarcopenia-related traits had causal effects on CD or RA.